The Apical Localization of Na+, K+-ATPase in Cultured Human Retinal Pigment Epithelial Cells Depends on Expression of the β2 Subunit - Lobato-Álvarez, Jorge A.; Roldán, María L.; López-Murillo, Teresa del Carmen; González-Ramírez, Ricardo; Bonilla-Delgado, José; Shoshani, Liora (Frontiers in Physiology, 2016)
Na+, K+-ATPase, or the Na+ pump, is a key component in the maintenance of the epithelial phenotype. In most epithelia, the pump is located in the basolateral domain. Studies from our laboratory have shown that the β1 subunit of Na+, K+-ATPase plays an important role in this mechanism because homotypic β1-β1 interactions between neighboring cells stabilize the pump in the lateral membrane. However, in the retinal pigment epithelium (RPE), the Na+ pump is located in the apical domain. The mechanism of polarization in this epithelium is unclear. We hypothesized that the apical polarization of the pump in RPE cells depends on the expression of its β2 subunit. ARPE-19 cells cultured for up to 8 weeks on inserts did not polarize, and Na+, K+-ATPase was expressed in the basolateral membrane. In the presence of insulin, transferrin and selenic acid (ITS), ARPE-19 cells cultured for 4 weeks acquired an RPE phenotype, and the Na+ pump was visible in the apical domain. Under these conditions, Western blot analysis was employed to detect the β2 isoform and immunofluorescence analysis revealed an apparent apical distribution of the β2 subunit. qPCR results showed a time-dependent increase in the level of β2 isoform mRNA, suggesting regulation at the transcriptional level. Moreover, silencing the expression of the β2 isoform in ARPE-19 cells resulted in a decrease in the apical localization of the pump, as assessed by the mislocalization of the α2 subunit in that domain. Our results demonstrate that the apical polarization of Na+, K+-ATPase in RPE cells depends on the expression of the β2 subunit.